PLEASE HELP I HAVE A FEW MORE LIKE THESE TO GO
![PLEASE HELP I HAVE A FEW MORE LIKE THESE TO GO class=](https://us-static.z-dn.net/files/d65/d866d4de8a4de545bea70e9eaceb6212.png)
Answer:
h(-4) = -3
h(-2) = -3
h(0) = -2
Step-by-step explanation:
We can see that the function's value is -3 for all numbers less than or equals to -2 and the function is (x-1)^2-3 between -1 and 1
So,
h(-4) = -3
As -4 is less than -2, so the value of function will be equal to -3.
h(-2) = -3
Similarly, on x=-2 the value of function will be -3.
And for h(0)
h(0) = (0-1)^2-3
= (-1)^2-3
=1-3
=-2
..